Exosomal miR-196b-5p is a potential diagnostic marker for colorectal cancer with metachronous liver metastasis - Wu, Jinhua; Lin, Bihua; Yu, Shuaishuai; Chen, Yingjie; Chen, Jianyong; Li, Caihong; Li, Xiangyong; Zhang, Xin; Liang, Yangfang; Zhou, Keyuan; Zeng, Jincheng (Translational Cancer Research, 2018)
Background: Accumulating data indicate that exosome-delivered microRNAs (miRNAs) play a key role in carcinogenesis and cancer progression. However, little is known about the influence of exosomal miR-196b-5p in the liver metastases of colorectal cancer (CRC). Methods: A total of 49 patients with non-liver metastases (NLM) CRC, 51 patients with synchronous liver metastases (SLM) and 50 patients with metachronous liver metastases (MLM) were enrolled and followed up in this study. Serum exosomal miR-196b-5p was determined by quantitative real-time polymerase chain reaction (qRT-PCR), and serum carcinoembryonic antigen (CEA), CA199 levels were detected by electrochemiluminescence. Then, outcomes of overall survival (OS) of CRC patients were estimated by Kaplan-Meier analysis. Finally, the areas under the receiver operating characteristic (ROC) curve of serum exosomal miR-196b-5p, CEA and carbohydrate antigen 199 (CA199) levels in CRC patient with liver metastases were assessed. Results: Serum exosomal miR-196b-5p was elevated in CRC patients and associated with liver metastases. Moreover, exosomal miR-196b-5p was positively correlated with CEA and CA199 in CRC patient with MLM. Additionally, CRC patients with higher levels of both serum exosomal miR-196b-5p and CEA, or both serum exosomal miR-196b-5p and CA199 showed a shorter OS. ROC analysis of serum exosomal miR-196b-5p in patients with SLM and MLM showed that the area under curve (AUC) were 0.6743 (95% CI: 0.5666–0.7820), higher than CEA [0.6294 (95% CI: 0.5197–0.7391)] and CA199 [0.5559 (95% CI: 0.4428–0.6689)], respectively. Conclusions: Our results suggest that serum exosomal miR-196b-5p could be a good diagnostic marker for CRC patient with MLM.